1991
DOI: 10.1113/jphysiol.1991.sp018780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of voltage and cyclic AMP on frequency of slow‐wave‐type action potentials in canine colon smooth muscle.

Abstract: SUMMARY1. A non-L-type calcium conductance is involved in the generation of the initial part of the slow-wave-type action potential in colonic smooth muscle. The present study addresses the question whether this conductance is voltage or metabolically activated.2. Current-induced hyperpolarization increased frequency and amplitude of slow waves measured in Krebs solution.3. The upstroke potential was 'isolated' from the slow wave by superfusion with 'glucamine-nitrendipine' Krebs solution (NaCl was replaced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…These cells are connected by numerous gap junctions to the smooth muscle. There have been a number of proposals regarding the generation of slow waves including: generation involving sodium pump activity (Connor et al, 1974), a Na'-Ca2" exchange mechanism (Tomita, 1981), metabolic activity (Huizinga et al, 1991) or a cardiac-like pacemaker cycle involving low threshold, voltage-dependent Ca2" channels (Lee & Sanders, 1993;Publicover, 1994). 1 Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…These cells are connected by numerous gap junctions to the smooth muscle. There have been a number of proposals regarding the generation of slow waves including: generation involving sodium pump activity (Connor et al, 1974), a Na'-Ca2" exchange mechanism (Tomita, 1981), metabolic activity (Huizinga et al, 1991) or a cardiac-like pacemaker cycle involving low threshold, voltage-dependent Ca2" channels (Lee & Sanders, 1993;Publicover, 1994). 1 Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…[41]. The model explains a number of features, including a role for the inward Ca 2+ current activated at negative potentials, the dependence of pacemaking on extracellular and on intracellular metabolic activity [42,43].…”
mentioning
confidence: 99%
“…Since these stimulators are known to inhibit slow wave and produce hyperpolarization, then suppressing contraction, it inhibits phasic contraction and basal tone in GI tract (Andersson and Nilsson, 1972;Jin et al, 1993;Smith et al, 1993). These findings imply that cyclic nucleotide activators such as FSK and SNP play an inhibitory role for basal tone as well as spontaneous contraction in human stomach (Huizinga et al, 1991;Ozaki et al, 1992;Jin et al, 1993;Smith et al, 1993;Kim et al, 2006;Kim and Perrino, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…β-Adrenergic nerve and VIP containing neurons in myenteric plexus, which project to the smooth muscle layers, have been reported to exist in the gut, and their stimulation inhibits slow wave and contraction via increasing cAMP and/or cGMP (Andersson and Nilsson, 1972;Jin et al, 1993;Smith et al, 1993). Furthermore, FSK and SNP, cyclic nucleotide (cAMP and cGMP) activators, have also been shown to inhibit electrical and contractile activity of GI smooth muscle (Huizinga et al, 1991;Ozaki et al, 1992;Jin et al, 1993;Smith et al, 1993;Kim et al, 2006;Severi et al, 2006). In the present study, we found the inhibitory effect of ISO in human stomach: ISO inhibited spontaneous contraction and basal tone in a reversible manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation